Odpowiedzi

2010-03-07T09:45:38+01:00
1/2x-4=x-6
1/2x-x=-6+4
-1/2x= -2 (podzielone)/:(-1/2)
x=4

x - 5 = 1/3 x + 1
x-1/3x=1+5
2/3x=6 /: 2/3
x=9

x/4 - 1/4 = 2 (razy)/* 4
4* x/4 - 4*1/4=4*2
x-1=8
x=9

x/5 -3 = x + 1/5 /*5
5*x/5-5*3=5x+5*1/5
x-15=5x+1
-4x=16 /:(-4)
x= -4

5/6 (x - 1 ) = 4
5/6x-5/6=4
5/6x=4 5/6 /: 5/6
x=5 i 4/5

- 1/2 ( - x -6 ) = x
1/2x+3=x
-1/2x=-3 /: (-1/2)
x=6
2 5 2
2010-03-07T09:47:54+01:00
A) 1/2x - 4 =x - 6 I +6
1/2x + 2 = x I - 1/2x
2 = 1/2x
x = 4
b) x - 5 = 1/3 x + 1 I +5
x = 1/3x + 6 I *3
3x = x + 18 I - x
2x = 18
x = 9
c) x/4 - 1/4 = 2 I * 4
x - 1 = 8 I + 1
x = 8
d) x/5 -3 = x + 1/5 I *5
x - 15 = 5x + 1 I + 15
x = 5x + 16 I - 5x
-4x = 16 I : -4
x = -4
e) 5/6 (x - 1 ) = 4 I * 6
5x - 5 = 24 I + 5
5x = 24 I :5
x = 24/5
x = 4 4/5
f) - 1/2 ( - x -6 ) = x I *2
x + 6 = 2x I - x
6 = x


:D Proszę bardzo! :D
1 1 1